2008
DOI: 10.28945/999
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Student Background in E-Learning — Longitudinal Study

Abstract: This study surveyed how students' backgrounds prepare them for online education. The study compared learning outcome between traditional and non-traditional (adult) undergraduate students in online and face-to-face sessions; the difference in learning over time; and the effect of prior online experience. Student learning measurements included: pre-test, final examination (post-test), and final letter grade. Findings revealed that online education is as effective as F2F sessions and that learning has occurred. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…We also found in the research literature that previous experience in e-Learning has a direct effect on learning outcomes, as well as students' perceptions of the learning process (Bennison and Goos, 2010; Boghikian-Whitby and Mortagy, 2008; Bouhnik and Carmi, 2013; Haverila, 2010). Therefore, prior experience of students with relevant online experience (in our study it will be listening to online podcasts) affects the efficacy of learning and the students' attitudes regarding e-Learning, in addition to determining the approach that students “go into the learning process with.” It is clear to us that, whereas previous experience can be beneficial in terms of its effectiveness and to increase positive attitudes, it is can also be detrimental.…”
Section: Literature Reviewsupporting
confidence: 64%
“…We also found in the research literature that previous experience in e-Learning has a direct effect on learning outcomes, as well as students' perceptions of the learning process (Bennison and Goos, 2010; Boghikian-Whitby and Mortagy, 2008; Bouhnik and Carmi, 2013; Haverila, 2010). Therefore, prior experience of students with relevant online experience (in our study it will be listening to online podcasts) affects the efficacy of learning and the students' attitudes regarding e-Learning, in addition to determining the approach that students “go into the learning process with.” It is clear to us that, whereas previous experience can be beneficial in terms of its effectiveness and to increase positive attitudes, it is can also be detrimental.…”
Section: Literature Reviewsupporting
confidence: 64%
“…Other definitions of effectiveness have been identified from extant literature as perceived learning, skills or competency obtained as a result of the e-learning process (Haverila, 2010; Jiang et al. , 2006), attitude toward e-learning (Boghikian-Whitby and Mortagy, 2008; Bennison and Goos, 2010), satisfaction obtained by participants (Harrington and Walker, 2009; Jung et al. , 2002; Maloney et al.…”
Section: Resultsmentioning
confidence: 99%
“…Creating the appropriate self-regulated learning environment and structure would regulate and reinforce the perceived learning outcomes for students (Eom and Ashill, 2018). Other definitions of effectiveness have been identified from extant literature as perceived learning, skills or competency obtained as a result of the e-learning process (Haverila, 2010;Jiang et al, 2006), attitude toward e-learning (Boghikian-Whitby and Mortagy, 2008;Bennison and Goos, 2010), satisfaction obtained by participants (Harrington and Walker, 2009;Jung et al, 2002;Maloney et al, 2011), skills acquired (Alinier et al, 2006) and the extent of learning retention by students (Hagen et al, 2011).…”
Section: Literature Selection Processmentioning
confidence: 99%
“…Many research studies suggested that effective SG should combine sound game design principles and learning theories with clear learning outcomes to enrich learning effectiveness (Amory & Seagram, 2003;Ibrahim et al, 2010;Lainema & Saarinen, 2010;Oblinger, 2006). Learning outcomes are considered the most significant indicator of learning effectiveness (Boghikian-Whitby & Mortagy, 2008). However, how SG assists in achieving learning outcomes is less clear due primarily to the scarcity of systematic investigations into the cognitive impact of SG (Annetta et al, 2009;Bellotti et al, 2013;Zolotaryova & Plokha, 2016).…”
Section: Learning Effectivenessmentioning
confidence: 99%